Interactive Interface for StarVZ Plot Visualization - Sousa Filho, Christian Einhardt; Pinto, Vinícius Garcia (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS), 2025)
This work introduces an interactive interface developed in R using the Shiny framework for visualizing plots generated by StarVZ. Visualization of execution traces is a key tool for performance analysis of parallel applications, helping to identify inefficiencies and optimize resource utilization. The interface allows users to load data, configure different visualization parameters, and switch between ggplot2 and plotly-generated graphs. The goal is to provide a more intuitive and flexible experience for execution trace analysis, making it easier to extract insights from processed data.